Message of Nationalism in the Music Video 'Wonderland Indonesia' - Teguh Dwi Putranto; Daniel Susilo (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2021)
Film is a communication medium that includes audio-visual types that are used to convey messages to a group of people watching. In addition to films, music videos which are also a medium of communication also convey messages in an audio visual work. One of the trending music videos during the celebration of the 76th Anniversary of the Republic of Indonesia (HUT RI) in 2021 is "Wonderland Indonesia". Through “Wonderland Indonesia” the landscape of Indonesia and the diversity of Indonesian culture is shown with epic cinematography. This study aims to determine how the message of nationalism in the music video "Wonderland Indonesia". The method used in this research is Charles Sanders Peirce's semiotics of the music video "Wonderland Indonesia" on Alffy Rev's YouTube Channel. The conclusion of this study is that the message of nationalism in the music video "Wonderland Indonesia" is so that the Indonesian people have a sense of devotion for Indonesia, have courage in defending Indonesia, self-determination so as not to be shaken, purity of heart, and have an unyielding spirit and a spirit that never goes out.Film merupakan media komunikasi yang termasuk jenis audio visual yang dimanfaatkan untuk menyampaikan pesan kepada sekelompok orang yang menyaksikan. Selain film, music video yang juga merupakan media komunikasi turut menyampaikan pesan dalam sebuah karya audio visual. Salah satu music video yang sedang trending selama perayaan Hari Ulang Tahun Republik Indonesia (HUT RI) ke-76 pada tahun 2021 ini adalah “Wonderland Indonesia”. Melalui “Wonderland Indonesia” pemandangan Indonesia dan keragaman budaya Indonesia ditampilkan dengan sinematografi yang epik. Penelitian ini bertujuan untuk mengetahui bagaimana pesan nasionalisme dalam music video “Wonderland Indonesia”. Metode yang digunakan dalam penelitian ini adalah semiotika Charles Sanders Peirce terhadap music video “Wonderland Indonesia” pada YouTube Channel Alffy Rev. Kesimpulan dari penelitian ini adalah bahwa pesan nasionalisme dalam music video “Wonderland Indonesia” agar masyarakat Indonesia memiliki rasa bakti bagi Indonesia, memiliki keberanian dalam membela Indonesia, ketegaran diri agar tidak tergoyahkan, kesucian hati, serta memiliki semangat pantang menyerah dan semangat yang tidak pernah padam.